A novel strictly anaerobic recovery and enrichment system incorporating lithium for detection of heat-injured Listeria monocytogenes in pasteurized milk containing background microflora. - Mendonca, A F (1994)
Heat-injured cells of Listeria monocytogenes were recovered from heated raw milk containing noninjured Enterococcus faecium by combining a simple method for obtaining strict anaerobiosis with a novel enrichment broth, Penn State University broth (PSU broth). Strictly anaerobic conditions were rapidly achieved by adding 0.5 g of filter-sterilized cysteine per liter to PSU broth and then purging the preparation with N2 gas. Little resuscitation or growth occurred in strictly anaerobic PSU broth without lithium chloride because of overgrowth by E. faecium. The growth of E. faecium decreased dramatically with increasing LiCl concentration; LiCl concentrations of 8 and 10 g/liter were completely bacteriostatic. The mechanism of inhibition by LiCl appeared to involve competition with the divalent cations Ca2+ and Mg2+. Heat-injured L. monocytogenes consistently recovered and grew rapidly in strictly anaerobic PSU broth containing 4, 6, or 7 g of LiCl per liter. The use of strictly anaerobic PSU broth containing 7 g of LiCl per liter permitted detection of severely heat-injured L. monocytogenes in one simple recovery-enrichment step by eliminating oxygen toxicity and inhibiting the growth of background microflora, without preventing the resuscitation and subsequent growth of heat-injured L. monocytogenes. L. monocytogenes heated in raw milk at 62.8 degrees C for 10, 15, and 20 min could be consistently recovered from strictly anaerobic PSU broth enrichment cultures at 30 degrees C after 48, 96, and 144 h, respectively, and hence, use of PSU broth may result in better recovery of both injured and noninjured cells from foods than currently used U.S. Department of Agriculture and Food and Drug Administration preenrichment procedures.